Effect of Low Dose Oral Contraceptive Pill on Glycemic and Lipidemic status in Women with Normal and Low BMI - Kasem, Setara Binte; Razzaque, Shaikh Abdur; Chowdhury, Towhidul Alam; Begum, Ferdousi; Adiba, Raisa; Anika, Selana; Ara, Rowshan; Ali, Liaquat (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s): Aim of the study was to explore the effect of the most widely used low dose OCP (Shukhi) on glycemic and lipidemic factors of under weight (Low BMI) Bangladeshi women. Materials and Methods: This case control study was conducted at the Department of Cell and Molecular Biology, Research Division, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic disorders (BIRDEM) and Family Planning Center of Dhaka Medical College Hospital during the period of Jan 2011 to Dec 2011. A total number of 40 women were included in this study having age range between 25-45 years. Twenty nine (29) were with normal BMI (>18.5) and 11 were with low BMI (<18.5) consuming Shukhi for six months to five years. The control group (n=29) constituted of women with normal BMI and the case group (n=11) constituted the women with low BMI ( BMI<18.5). Both groups use low dose OCP (30?g ethinyl estradiol and 150 ?g levonorgestrel for 6-60 months. Glycemic status was assessed by measuring blood glucose fasting and 2 hrs after 75g glucose, insulinemic status by measuring C-peptide and lipidemic status by measuring TG, T Chol, HDL, LDL. Results:There was no significant differences between two groups in fasting blood glucose and two hours after 75g glucose. A significantly high C-peptide (p=0.043) level was found in low BMI users, but a significantly negative correlation was found between fasting blood glucose and BMI in underweight OCP users (r=622, p=0.041). A better insulin sensitivity was found in low BMI as compared to normal BMI. Significantly lower total cholesterol (p=0.018) and LDL cholesterol (p=0.017) levels were found in low BMI OCP users than those of normal BMI OCP users. However, no significant correlation existed between any lipids. Conclusion: This study suggested that OCP dont affect the glycemic, insulinemic ( insulin secretory and sensitivity) and lipidemic status of underweight subjects. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(2) : 65-72